PROMOTING THE COMPETITIVENESS OF TASIKMALAYA UMKM THROUGH STRATEGIES FOR PRODUCT INNOVATION DEVELOPMENT - Nurhutami, Meita Annisa; Mu’minah, Afifah; Yamin, Alfian Azhar; Pahrulroji, Andri; Insani, Handayani Madania (Universitas Sahid, 2024)
This program aims to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Tasikmalaya through product innovation development strategies. This program adopts an interdisciplinary approach that includes several stages, from identifying needs to evaluating performance. The main activities carried out include local potential analysis, technical and managerial skills training, innovation assistance, and product evaluation. The results achieved from this program include innovative product prototypes, publication of scientific articles, video documentation, and draft Intellectual Property Rights (IPR). This program proves that collaboration based on science and technology can empower MSMEs, encourage the development of more competitive products, and support sustainable local economic development.